PENGARUH METODE MUROJA’AH TERHADAP BACAAN AL-QUR’AN SANTRI NON TAHFIDZ DI PONDOK PESANTREN PUTRI WALISONGO CUKIR JOMBANG - Khatami, Meizia; anshori, Sholihul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students at Walisongo Cukir Jombang Girls' Islamic Boarding School who are not tahfidz were the subjects of this study, which aimed to determine whether the muroja'ah method may increase their capacity to read the Al-Qur'an. Their female teachers' concerns about the students' reading comprehension of the Al-Qur'an prompted this study. The students' reading fluency and uninterrupted passages, their pronunciation of hijaiyah letters correctly according to their place of sound (makharijul huruf), and their ability to apply the rules of tajwid science were the three main dimensions examined. A quantitative methodology based on a quasi-experimental design was utilised in this work. Researchers were able to gauge the treatment's efficacy by comparing the two groups' final assessment scores using a posttest-only control group approach. Two sets of sixteen students each made up the sample. There were twenty-five pupils in the experimental group and twenty-one in the control group. A purposive sampling strategy was utilised for the sample selection. Validity and reliability analyses had already been conducted on the research instrument, which was a test of Qur'an reading. A significance level of 0.000 (<0.05) was observed in the hypothesis test utilising the Mann-Whitney U, leading to the rejection of H₀ and acceptance of H₁. The fact that the experimental group averaged 81.48 points and the control group 70.19 points lends credence to this finding. As a result, non-tahfidz students' Qur'an reading abilities were significantly enhanced by the muroja'ah technique, particularly in the areas of fluency, letter pronunciation, and the use of tajwid